Ideological Contestations of Salafism and Moderatism in Indonesia's Hijra Movement: Critical Discourse Analysis - Khamdan, Muh; Wiharyani; Abidin, Nadiah (UIN Kiai Haji Achmad Siddiq Jember, 2024)
The new pattern of learning for Indonesian Muslims, preferring references to religious knowledge through digital media, provides opportunities for Salafi groups to propose their religious teaching and movements, such as through Islamic-based websites, to contend in religious discourse. Ultimately, Islam experiences ideological contestation, including the construction of the hijra movement through a socialized understanding of Islamic law. This article explores the discourse of the hijra movement applied Salafism using Norman Fairclough's critical discourse analysis, which focuses on text, practice, and socio-cultural analysis. Therefore, the research data includes affiliated online publications and religious practices observed in Salafism religious forums in Bogor, Depok, and Jakarta. The results demonstrated that the hijra movement through digital media has become a strategic arena for the Salafi group in disseminating the Puritan narrative among middle-class Muslims, while Moderatism prioritizes tolerance and pluralism. Salafi group succeeded in captivating these Muslims who preferred to acquire Islamic understanding through online media rather than traditional religious forums to profess Salafism even though of internal conflict within Salafism. This study highlights the need for strengthening digital literacy to investigate ideological interactions across diverse Islamic groups in digital spaces.